Activity level and body mass index: An analysis of the Canadian Forces Health and Lifestyle Information Survey - Bennett, Carol L (University of Ottawa (Canada), 2005)
The increasing prevalence of overweight status and obesity among the general population is a major public health concern. There is debate surrounding the role of recreational physical activity in the prevention of weight gain at the population level. This study examined the cross-sectional association between overweight status and obesity and recreational physical activity in a large representative sample of members of the Canadian Armed Forces (n = 4749) using polytomous logistic modelling. A systematic review of the literature looking at the longitudinal relationship between activity level and body mass was conducted and a health promotion intervention was developed. After adjustment for several significant covariates, recreational energy expenditure was significantly and inversely associated with the prevalence of class I obesity compared to normal weight classification (OR 0.94, 95% CI 0.90-0.97), but was not significantly associated with the odds of having a BMI classified as either overweight or obese class II/III (OR 1.01, 95% CI 0.98-1.03; OR 0.93, 95% CI 0.85-1.02) versus having a BMI classified as normal. This study suggests efforts to prevent overweight status and obesity at the population level could profitably address physical activity habits but need to consider the multi-factorial nature of the problem.
Keywords: Health Sciences, Public Health.